Gangguan Autisme dan Penatalaksanaan Psikiatrik - Warsiki, Endang (Faculty of Psychology, Universitas Surabaya, 2007)
The onset of autistic disorder in children happens before 36 months and manifests in three main symptoms i.e. failure in social interaction, verbal and nonverbal communication, lack of interest and repeated behavior. There are three basic types in autistic disorder: Classic autism (Kanner syndrome), regression autism, and secondary autism. The cause of autism is mainly a neurobiologic factor with or without genetic predisposition. Environmental triggers such as subclinically virus infection and/or heavy metal intoxication such as Hg, Pb, Cd, As, Al could ignite autistic symptoms causing disfunction of metallothionein (MT). The function of MT is to modulate the arrangement of behavior, memory, emotion, and socialization. The psychiatric management of autistic children comprises medicamentous, behavioral, speech, occupational therapy and special education. Gangguan autisme pada anak timbul sebelum usia 36 bulan dan meliputi tiga gejala utama yakni kegagalan dalam interaksi sosial, komunikasi verbal dan nonverbal, serta terbatasnya minat dan tingkah laku yang berulang. Ada tiga tipe dasar gangguan autisme: Autisme klasik (sindroma Kanner), autisme regresif, dan autisme sekunder. Penyebab autisme terutama adalah faktor neurobiologis dengan atau tanpa predisposisi genetik. Pemicu lingkungan seperti infeksi virus subklinis dan/atau keracunan logam berat seperti Hg, Pb, Cd, As, Al dapat memicu timbulnya gejala autisme yang menyebabkan terjadinya disfungsi dari metallothionein (MT). Fungsi MT memodulasi pengaturan tingkah laku, memori, emosi dan sosialisasi. Penatalaksanaan psikiatrik pada anak dengan autisme meliputi terapi medikamentosa, perilaku, wicara, okupasi dan pendidikan khusus.